Review of 20 Years of Continuous Quality Improvement of a Rapid Response System, at Four Institutions, to Identify Key Process Responsible for Its Success. (10th August 2021) - Vandegrift, Mary Anne; Granata, Robert; Totten, Vicken Y.; Kellett, John; Sebat, Frank
Abstract : BACKGROUND: Rapid response systems are still in development, and their practices vary significantly from hospital to hospital. Although the literature supports their value and a four-arm structure, it is unclear within these arms (efferent, afferent, quality assurance, administrative arms) which processes and procedures are responsible for their efficacy. This article reports the evolution of a rapid response system over many years at four institutions and considers the key elements that likely contribute to its efficacy. METHODS: Retrospective evaluation of the processes, procedures, and outcomes of an adult general-ward rapid response system as it evolved, at four nonaffiliated community medical centers, spanning 2 decades of development and refinement. System and patient outcomes examined included the number of rapid response system activations/1, 000 admissions, time to rapid response system activation and/or interventions, cardiac arrest rate, and/or hospital mortality over time. RESULTS: In the three hospitals that collected control and intervention data, there was significant increase in earlier and total number of rapid response system activations, more rapid administration of protocolized interventions, and associated decreases in cardiac arrest rate and hospital mortality of the respective population. In all four institutions three important common rapid response system processes were identified: early identification of at-risk patient using a novel focused bedside-assessment tool, leading to classification of the pathophysiologic process, linked to goal-directed intervention protocols. CONCLUSIONS: Our review of a rapid response system that evolved over 20 years across four unrelated institutions revealed a common care pathway that coupled a focused bedside at-risk patient assessment leading to pathophysiologic classification of the patients decline linked to goal-directed intervention protocols. We speculate that the improved outcomes observed are a consequence of effective implementation and coupling of these three processes, as they are important in identifying and treating early the signs of tissue hypoxia and hypoperfusion, which remain the basic pathophysiologic threats of acute deterioration.